Dynamics associated with spontaneous differentiation of ovarian stem cells in vitro - Parte, Seema (J Ovarian Res, 2014)
BACKGROUND: Recent studies suggest that ovarian germ line stem cells replenish oocyte-pool in adult stage, and challenge the central doctrine of ‘fixed germ cell pool’ in mammalian reproductive biology. Two distinct populations of spherical stem cells with high nucleo-cytoplasmic ratio have been recently identified in the adult mammalian ovary surface epithelium (OSE) including nuclear OCT-4A positive very small embryonic-like (VSELs) and cytoplasmic OCT-4 expressing ovarian germ stem cells (OGSCs). Three weeks culture of scraped OSE cells results in spontaneous differentiation of the stem cells into oocyte-like, parthenote-like, embryoid body-like structures and also embryonic stem cell-like colonies whereas epithelial cells attach and transform into a bed of mesenchymal cells. Present study was undertaken, to further characterize ovarian stem cells and to comprehend better the process of spontaneous differentiation of ovarian stem cells into oocyte-like structures in vitro. METHODS: Ovarian stem cells were enriched by immunomagnetic sorting using SSEA-4 as a cell surface marker and were further characterized. Stem cells and clusters of OGSCs (reminiscent of germ cell nests in fetal ovaries), were characterized by immuno-localization for stem and germ cell specific markers and spontaneous differentiation in OSE cultures was studied by live cell imaging. RESULTS: Differential expression of markers specific for pluripotent VSELs (nuclear OCT-4A, SSEA-4, CD133), OGSCs (cytoplasmic OCT-4) primordial germ cells (FRAGILIS, STELLA, VASA) and germ cells (DAZL, GDF-9, SCP-3) were studied. Within one week of culture, stem cells became bigger in size, developed abundant cytoplasm, differentiated into germ cells, revealed presence of Balbiani body-like structure (mitochondrial cloud) and exhibited characteristic cytoplasmic streaming. CONCLUSIONS: Presence of germ cell nests, Balbiani body-like structures and cytoplasmic streaming extensively described during fetal ovary development, are indeed well recapitulated during in vitro oogenesis in adult OSE cultures along with characteristic expression of stem/germ cell/oocyte markers. Further studies are required to assess the genetic integrity of in vitro derived oocytes before harnessing their clinical potential. Advance in our knowledge about germ cell differentiation from stem cells will enable researchers to design better in vitro strategies which in turn may have relevance to reproductive biology and regenerative medicine.